The Influence of Information System, Internal Control System, and Understanding Regulation on The Effectiveness of Regional Asset Management, with The Quality of Regional Aparatures as A Moderating Variables in Pekanbaru City Government - Yuswanita, Lativa; Basri, Yesi Mutia; Nasrizal, Nasrizal (Program Pascasarjana, Universitas Riau, 2019)
This study aims to find the empirical evidence of the influence of information system, internal control system, and understanding regulation on the effectiveness of regional asset management, using the quality of the regional apparatus as a moderating variable. The population in this study is Regional Apparatus Organization (OPD) located in Pekanbaru City Government. The total of population is 44 OPDs. The sampling technique in this study is saturated sampling technique. Thus, there are 44 OPDs that becomes sample in this study. The data used is primary data, while the data analysis method is Structural Equation Model (SEM) approach using WarpPLS software version 6.0. The results of this study concluded that information system, internal control system and understanding regulation affect the effectiveness of regional asset management. The quality of regional apparatus is able to moderate the information system, internal control system and the understanding regulation on the effectiveness of regional asset management.